Penggunaan Preposisi di, pada, dan dalam: Sebuah Studi Sintaksis dalam Ragam Bahasa Jurnalistik Berbasis Korpus - Chasanah, Lisa Nur (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2025)
Preposition is a word that functioning for laying down words, phrases, or clauses. The aim of this research was to know the frequency, determine colligation patterns, and describe the syntactical roles of prepositions ‘di’, ‘pada’, and ‘dalam’ in a range of language used in journalism with a corpus-based syntactic approach. This study is a qualitative descriptive, taking out corpus-based data in the forms of prepositions ‘di’, ‘pada’, and ‘dalam’. The data sources for this research were taken from 21 online news articles during August-September 2023, with the keyword that thesis was not mandatory. The data were collected using the corpus method utilizing the AntConc application version 3.5.9. Once the data were collected, four stages were performed: data reduction, data presentation, data verification, and data analysis. The results of data analysis was formally presented in the form of diagrams and tables and informally in the form of descriptions or descriptions. This study found the difference in the frequency of the three prepositions was quite enormous; the preposition ‘di’ was found 192 words, the preposition ‘pada’ was counted 60 words, and the preposition ‘dalam’ was 119 words. The colligation pattern of prepositions ‘di’, ‘pada’, and ‘dalam’ was mostly followed by non-persona nouns and least followed by nominal phrases or persona nouns. In journalistic language varieties, prepositions ‘di’ and prepositions ‘pada’ have syntactic roles of temporal, spatial, and recipient, while prepositions ‘dalam’ have no syntactic role of the recipient.